Technique of 'suture less' appendicectomy by laparoscopy in children: Preliminary communication - Minu Bajpai (Wolters Kluwer Medknow Publications, 2014)
Objective: Objective of this study is to present our experience by harmonic scalpel enabled, single external port appendicectomy using extracorporeally inserted 'pick and fix' stitch in three cases. Materials and Methods: Of the eighteen appendicectomies performed with only the use of harmonic scalpel in the last 11 months, the last three were performed using a single external port with the second port accessed under the subcutaneous tissues. The procedure consists of anchoring the mesoappendix to anterior abdominal wall by an extracorporeally inserted 'pick and fix' stitch followed by dissection and division of mesoappendix and appendix only with harmonic scalpel. Results: There were three patients, one female and two males aged 5, 7, and 11 years, respectively. Two were elective and one was emergency appendicectomy. Mean operating time was 30 min without any surgical complications. All patients are in follow-up with no complications. Conclusion: This study demonstrates the combined virtue of single external port, use of harmonic scalpel, and 'pick and fix' suture in laparoscopic appendicectomy in children. This approach avoids the use of an additional port as well as endosuture; and is safe, efficient, cost-effective, and is associated with reduced surgical time.